Determination of the optimal critical amplitude dvudiapazonnogo for photometric conversion - Саваневич, Вадим Евгеньевич; Кожухов, Александр Михайлович; Брюховецкий, Александр Борисович; Власенко, Владимир Петрович; Ткачев, Виталий Николаевич (Eastern-European Journal of Enterprise Technologies, 2011)
The method of determination of optimal critical amplitude’s value for getting the best coefficients of double-band photometric scaling model is developed. The method has used by authors in developed system of automatic online new asteroids detection and known asteroids tracking CoLiTec. The results of method application is presented